2012
DOI: 10.1590/s0101-31222012000100018
|View full text |Cite
|
Sign up to set email alerts
|

Vigor de sementes e desempenho de plantas de milho

Abstract: RESUMO -Estudou-se os efeitos da utilização de lotes constituídos por sementes de milho de alto ou de baixo vigor, bem como a mistura desses em diferentes proporções, simulando-se o uso de lotes de sementes homogêneos e heterogêneos quanto ao vigor das sementes, sobre o crescimento inicial e produtividade das plantas. Observou-se que plantas originadas de sementes menos vigorosas foram inferiores às originadas de sementes mais vigorosas quanto ao crescimento inicial e, para os componentes de produção, as prove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 26 publications
(15 reference statements)
2
10
0
1
Order By: Relevance
“…Similar results about the effects of vigor in grain production were found on soybean by and Tavares et al (2013), on irrigated rice by Höfs et al (2004) and Mielezrski et al (2008) and on maize by Ludwig et al (2009) and Mondo et al (2012;.…”
Section: Resultssupporting
confidence: 76%
“…Similar results about the effects of vigor in grain production were found on soybean by and Tavares et al (2013), on irrigated rice by Höfs et al (2004) and Mielezrski et al (2008) and on maize by Ludwig et al (2009) and Mondo et al (2012;.…”
Section: Resultssupporting
confidence: 76%
“…According to Silveira et al (2005), one of the characteristics that most contribute to adequate plant stand and to improvement of crop yield is uniformity of the longitudinal distribution of seeds. Thus, an individual within a population experiences the effects of restriction on growth rate according to the presence and arrangement of neighbors in the plant population (Mondo et al, 2012). More equidistant distributions reduce these effects of restriction and contribute so that plants more completely and efficiently utilize the resources of a determined soil area (Freitas et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…This characteristic is important in breeding programs, for it is an effective indicator of the common bean plant architecture (Moura et al, 2013). In greater longitudinal distances between plants, there is likely less competition, and this favors greater absorption of nutrients, sunlight, and water, with a positive effect on yield (Mondo et al, 2012). Azevedo et al (2008) observed increases in the number of pods per area, 100 grain weight, and grain yield of common bean as the number of plants per area declined.…”
Section: Resultsmentioning
confidence: 99%
“…For Schuch et al (2000), differences in vigor of black oat seeds affected only the initial plant growth, and the effects of seed vigor were reduced as the crop developed. Mondo et al (2012) also suggest that the influence of seed vigor is reduced in developmental stages of the plants, and the plant response varies according to genotype and environmental relations.…”
Section: Resultsmentioning
confidence: 99%